Serrated Glass Facades: the Influence of Façade Morphology on Aesthetic Quality - Marcin Brzezicki (Challenging Glass Conference, 2018)
Serrated building envelopes are a very eye-catching element of contemporary architecture. This type of façade in plan resembles the edges of a serrated blade, hence the name. Serrated facades substantially influence the building’s tectonics understood as the relationship between the structural and the artistic form. They also have a major impact both on building physics (increased surface of heat exchange compared to flat facades, solar avoidance – decreased solar gains if properly designed) and on visual appeal. This article examines façade morphology and analyzes the influence of its geometry on the aesthetic quality of the envelope. The morphological analysis includes the serration angle between the wings (acute or obtuse), wing proportions, and façade depth. An exceptional feature of serrated façades is that the optical phenomena on the façade change depending on the viewing angle. This paper discusses various perceptual zones that produce different phenomena, e.g.: (i) single wing visibility, (ii) mutual wing self-reflection, (iii) primary and secondary virtual The presented paper is based on case studies with special attention to morphological and qualitative analysis. Cases serve as visual (photographs) and graphical illustrations(diagrammatic drawings). The paper also includes a brief presentation of selected recently completed case studies.